A Faustain Bargain? Nuclear Weapons, Negative Security Assurances, and Belligerent Reprisal - McCarron, Paula B.; Holt, Cynthia A. (Tufts Archival Research Center, 2005)
Volume 25, Issue 2. Summer McCarron and Holt analyze the legality of the use of nuclear weapons by exploring specific and general treaty prohibitions and customary international law.